0036 Sleep, Inflammation and Telomere Length. (27th April 2018) - Knowles, S; Slavish, D; Cyrus, A; Arnetz, B
Abstract: Introduction: Prior studies have reported an association between sleep, inflammatory cytokines, and telomere length, as well as an association between telomere length and various diseases. Fatigue, perceived stress, combat status and PTSD have also been associated with shorter telomere length. This pilot study evaluated the effect of total sleep time (TST), inflammatory cytokines, and telomere length (TL) in veterans, to explore whether TST or sleep quality predicts TL via inflammation. Methods: Eleven veterans who had a prior polysomnogram (PSG) participated (mean age = 51 years; 2 female; mean AHI (apnea-hypopnea index) = 13/hr, mean BMI = 29.9). Inflammatory cytokines (hsCRP, IL-6, and TNF-alpha) and TL were measured. Fatigue, perceived stress, and sleep quality were measured using validated scales. Data were analyzed using multiple linear regression, and all models controlled for age, gender, and BMI. Effect sizes were evaluated by examining squared semi-partial correlations (sr 2 ). Results: Contrary to our hypothesis, inflammatory cytokines did not mediate the relationship between TST and TL. Instead, TST and AHI both directly predicted TL independent of covariates (TST: b = 892.11, p < .01; AHI: b = 117.07, p < .01). However TST had a stronger effect (sr 2 = .55) on TL than age (sr 2 = .42), gender (sr 2 = .06), BMI (sr 2 = .19), and AHI (sr 2 = .23). PTSD, combat status, perceived stress, and sleep quality did not predict TL. Greater levels of fatigue predicted higher hsCRP (b = 0.02, p < .01, sr 2 = .41), but neither fatigue nor hsCRP was associated with TL. Conclusion: This study was the first to examine inflammation as a mediator between sleep and TL in veterans. Results suggest that objectively measured TST is the most robust predictor of telomere length, independent of several health related and psychosocial variables. The AHI-TL relationship may be complex. Results should be replicated in a larger sample, but this pilot study suggests the need for further research examining sleep duration as a unique risk factor for premature aging in veteran populations. Support (If Any): Metropolitan Detroit Research and Education Foundation.